CHINESE MIGRATION IN KAZAKHSTAN: IMPLICATIONS FOR NATIONAL SECURITY - Svetlana Kozhirova; Bakyt Ospanova (European Scientific Journal, ESJ, 2014)
This paper intensively discusses Chinese migration to Kazakhstan as possible threat to national security. Authors argue that Chinese demographic expansion is regarded as threat in public discourse of the country. This could be explained by several factors: general influx of foreigners into country since independence; incoming Chinese labor as a part of Chinese FDI into Kazakh economy; and general trend of export of Chinese labor force surplus, which Central Asian countries expect to receive at least partially. However, the analysis of empirics reveals that the number of Chinese migrants in Kazakhstan is marginal. Moreover, they do not intent to stay in Kazakhstan for long or acquire citizenship.